An Overview of COVID-19 Patients in RSUD Bhakti Dharma Husada Surabaya from September 2020 to June 2021 - Trisnawati, Yunika; Firman Suryadi Rahman (Indonesian Journal of Tropical and Infectious Disease, 2022)
The COVID-19 pandemic has been lasting more than a year. Until now, research on the analysis of an overview of COVID-19patients has not been carried out at RSUD Bhakti Dharma Husada Surabaya. This study aims to describe the COVID-19 cases in RSUD Bhakti Dharma Husada Surabaya about the gender of patients, highest number of patients, the most recovered patient, the highest death rate occurred, and Case Fatality rate (CFR). This study is a descriptive observational study with a case series approach. The data used in this study were COVID-19 data from the application of online Hospital ditjen yankes from September 2020 to June 2021. The majority of COVID-19 cases occured in women (53.04 %). The COVID-19 patients mostly came to the hospital in June 2021, about 241. The most recovered patients in Oktober were 255 patients. The highest death rates occurred in June 2021 ware 47 patients. Case Fatality rate (CFR) is at 5.79 % because in June 2021 the health facilities were full, and cause patients did not get help quickly. Many patients have been forced to self-isolate at home so that they have worsened and ï¬ nally died. Most COVID-19 patients who were treated at the RSUD Bhakti Dharma Husada Surabaya from 2020 to June 2021 occurred in women and the most patients who were admitted was in June 2021.